Synergistic effect in the reduction of Cr(VI) with Ag-MoS2 as photocatalyst. (March 2020) - Sun, Kaige; Jia, Feifei; Yang, Bingqiao; Lin, Changsheng; Li, Xianghui; Song, Shaoxian
Graphical abstract: Highlights: A new mechanism of the reduction of Cr(VI) with Ag-MoS2 as photocatalyst is revealed. Reduction of Cr(VI) is due to synergistic effect through chemical and photocatalytic reduction of Ag-MoS2 . The introduction of Ag nanoparticles on MoS2 can enhance the photocatalytic efficiency. Abstract: In this work, Cr(VI) reduced into Cr(III) in aqueous solution with Ag-MoS2 as photocatalyst has been studied in order to approach into the mechanism of the reduction. The results have shown that the mechanism was not only due to the photocatalytic reduction through excited photoelectrons by Ag-MoS2, but also attributed to the chemical reduction (redox reaction) from the self-oxidation of MoS2 nanosheets. This synergetic effect is not reported elsewhere. In dark condition, chemical reduction played a predominant role, in which MoS2 acted as an electron donor through its self-oxidation, while Cr(VI) anions were electron acceptor. In visible light condition, photocatalytic reduction started working, in which photoexcited electrons had an effective impact on Cr(VI) reduction, while chemical reduction also played a role. This finding might be really significant for the application of MoS2 as an effective photocatalyst for the reduction of Cr(VI).